PENGARUH PELATIHAN, DISIPLIN KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA ORGANISASI PADA KANTOR WILAYAH DIREKTORAT JENDERAL KEKAYAAN NEGARA KEMENTERIAN KEUANGAN REPUBLIK INDONESIA DKI JAKARTA - Alchintia Putri Wahyudi, (2022)
This research uses a quantitative method that aims to determine and prove the effect of training, work discipline, and job satisfaction on organizational performance. The sample in this study were 68 employees of the Regional Office of the Directorate General of State Assets DKI Jakarta. Data was collected through questionnaires distributed to employees of the Regional Office of the Directorate General of State Assets DKI Jakarta using the Google Form. Testing of the data in this study using the SmartPLS 3.0 test tool. The test results show that (1) training has a significant effect on organizational performance, (2) work discipline has a significant effect on organizational performance, (3) job satisfaction has no significant effect on organizational performance, and (4) training, work discipline, and job satisfaction have an effect significant simultaneously on organizational performance.